PERPSPEKTIF HUMAN RELATION DALAM PENYELESAIKAN KONFLIK OLEH SERIKAT PEKERJA PADA INDUSTRI PARIWISATA DI KABUPATEN BADUNG - Putri Ekaresty Haes; I Wayan Joniarta (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2020)
This article discussed conflicts that occurred in the tourism industry. The techniques of collecting data that used were through observation, unstructured interviews and documentation. While the data analysis technique used several stages, namely the stages of data reduction, data display and conclusions and verification. The results of the study stated that (1) conflicts that occur in the industry are internal conflicts, this dispute appeared because of the failure of two parties (workers and management or between units) in conveying thoughts, ideas, feelings and actions to the cause of not achieving equality of meaning (mutual understanding) resulted in wrong perceptions between both parties. The difference in meaning in the message conveyed occurs because there were different interpretations between communication style (2) transformational leadership can support the presence of internal conflict in organizations. (3) Several cases of internal conflict that occur in the industry discussed at LKB is an institution that aims to create an atmosphere of effective organizational communication and a conducive work climate.